Impact of beta-naphthoflavone on genotoxicity of food-derived carcinogens - Hodek, Petr; Krizkova, Jitka; Frei, Eva; Singh, Rajinder; Arlt, Volker M.; Stiborová, Marie (Neuroendocrinology letters, 2011)
OBJECTIVES: Benzo[a]pyrene (BaP) and 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) are carcinogens, which frequently occur in the human diet. Their metabolic activation to reactive species binding to DNA is mediated by cytochromes P450 (CYPs) 1A1 and 1A2. Thus, levels and activities of these CYPs are crucial for initiation of BaP- and PhPI-mediated carcinogenesis. Here, the effect of CYP1A1/2 induction due to their prototype flavonoid inducer, β-naphthoﬂavone (BNF), on BaP- and PhPI-derived DNA adduct formation in rats was examined. - METHODS: Male rats pretreated with BNF were treated with a single dose of either carcinogen by oral gavage. Nuclease P1 version of 32P-postlabeling assay and online column-switching liquid chromatography-electrospray ionization-tandem mass spectrometry were used to detect and quantify covalent DNA adducts formed by BaP and PhIP in-vivo, respectively. Expression of CYP1A1/2 enzymes was examined by Western blot. Enzymatic activities of CYP1A1/2 were assessed using their marker substrates (ethoxyresorufin and methoxyresorufin). - RESULTS: Treatment of rats with a single dose of BNF produced an increase in levels CYP1A1/2 and CYP1A1 proteins in liver and small intestine, respectively. An increase in CYP1A1 protein expression found in both organs correlated well with specific activities of these CYPs. The CYP1A1 expression levels and its specific activity in small intestine decreased along the length of the organ, being highest in its proximal part and lowest in its distal part. The BNF induction of CYP1A1/2 resulted in a significant increase in the formation of BaP- and PhIP-DNA adducts in liver and in the distal part of the small intestine, respectively. Thus, pretreatment of rats with BNF did not prevent the PhIP and BaP activation, but vice versa, enhanced their genotoxicity. - CONCLUSIONS: The results of this study demonstrate that the administration of only a single dose of CYP-inducing flavonoid prior to the intake of food carcinogens may increase the risk of a tumor formation.